Significance of Comparing Electoral Systems: Indonesia and the United Kingdom - Murdani, Anisya; Arbaita, Emilia Rifa; Satizzainiyah, Nisa'atur Riya; Zaini, Zaini (CV. Pustaka Parawali, 2024)
Elections are a mechanism that allows people to voice their choices. This process is used as a tool to exercise sovereignty in the country's system of representative democracy and to maintain government power in an orderly and peaceful manner by the mechanisms determined by the constitution or applicable laws. This paper will discuss the electoral systems in Indonesia and the United Kingdom (UK) and compare the two. Based on research into the law, it is known that Indonesia's electoral system uses a proportional system, which calculates the number of seats based on the number of voters in the electoral district. Countries with large populations will get more seats in representative bodies. Meanwhile, the UK uses a majoritarian system or District System, where each electoral district has only one seat with a simple majority calculation (simple majority: A>B>C>D, where A is the winner).